Identification of Spring Quality Using Tree and Insects Data Collection - Semiun, Chatarina; Mamulak, Yulita Iryani; Pani, Emilianus (Universitas Djuanda, 2025)
Spring water quality is important for human health, so it needs to be preserved. The study aimed to identify spring water quality by approaching the data collection of tree species and insects that live in the spring area. The study was conducted in two springs in T and M villages, Kupang Tengah sub-district, Kupang regency. The study was descriptive, using a random systematic sampling method to obtain data on tree species, insect species, and spring water quality. Data on tree species and insects were analysed descriptively, while water quality data were compared with water quality standards according to Government Regulation No. 22 of 2021. The study found that 14 types of trees and 11 types of insects inhabited the springs. The water quality of the two villages met the physical parameter quality standards but not yet for chemistry and microbiology. Village T had not met the dissolved oxygen (DO) quality standards for categories I and II, while Village M had not met the biological oxygen demand (BOD) quality standards for category I. The water quality from the physical and chemical aspects was still suitable for community activities such as bathing, agriculture, fisheries, and animal husbandry. However, it must first be processed (cooked until boiling) for direct consumption.